1988
DOI: 10.1037/0033-2909.103.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Induced movement in the visual modality: An overview.

Abstract: Induced movement, illusory movement in a stationary stimulus resulting from adjoining movement, has received steady experimental investigation over the last 70 years or so. It is observed under different viewing conditions in a wide variety of displays that differ considerably in overall size and in form of inducing and induced stimuli. Explanations have been diverse, some being based on relations within the display and others invoking mediation by other aspects of the observer's perception. Probably, no one e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 180 publications
(562 reference statements)
2
51
0
Order By: Relevance
“…Induced movement is most effectively elicited when induced and inducing stimuli are as close as possible in all three dimensions of space (adjacency principle: Gogel & Koslow, 1972;Gogel & MacCracken, 1979;Reinhardt-Rutland, 1988), whereas motion parallax increases with increasing distance between two objects. As a consequence, if the contradirectional sway observed in foreground fixation condition (Experiment 1) was elicited by induced movement of the foreground, it should be even greater and more consistent when the earth-fixed foreground is coplanar with the moving background than when the foreground and background are at 100 cm from each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced movement is most effectively elicited when induced and inducing stimuli are as close as possible in all three dimensions of space (adjacency principle: Gogel & Koslow, 1972;Gogel & MacCracken, 1979;Reinhardt-Rutland, 1988), whereas motion parallax increases with increasing distance between two objects. As a consequence, if the contradirectional sway observed in foreground fixation condition (Experiment 1) was elicited by induced movement of the foreground, it should be even greater and more consistent when the earth-fixed foreground is coplanar with the moving background than when the foreground and background are at 100 cm from each other.…”
Section: Methodsmentioning
confidence: 99%
“…A perceived movement of the fixated foreground induced by the moving background ("induced movement"; see Reinhardt-Rutland, 1988, for review) could also be responsible for the contradirectional sway observed by Bronstein and Buckwell (1997). Van Asten et al (1988) investigating visually induced body sway in the anteroposterior direction reported that when the central part of their linearly moving display was masked, anteroposterior sway was in the opposite direction of background motion (moving forward -backward) in 25% of the trials.…”
mentioning
confidence: 99%
“…Copyright 1990 Psychonomic Society, Inc. -Rutland, 1988), it is unlikely that each of the proposed visual-vestibular causes of 1M operate under all conditions in which 1M is observed. Specifically, with small inducing stimuli, which are incapable of eliciting vection, it is unlikely that vection sensations contribute to 1M.…”
mentioning
confidence: 99%
“…A number of stimulus variables can be identified that reduce or promote induced motion. For example, induced motion diminishes when the motion of the inducing pattern increases in speed (36) . Another critical condition for induced motion is that the frame that defines the background and the enclosed stimulus should be adjacent to one another, i.e.…”
Section: Induced Motion Autokinesismentioning
confidence: 99%
“…In this case, however, a displacement of sound opposite to the direction of visual motion adaptation can be observed, suggesting a cross-modal, visual-auditory aftereffect (49) . Motion aftereffects can also be obtained from (and interact with) induced motion (36) . These and other findings (50) indicate the existence of several different motion aftereffects, depending upon the site at which adaptation effects occur.…”
Section: Motion Adaptation and Aftereffectsmentioning
confidence: 99%